Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung Bawah pada Ibu Hamil Trimester II dan III di BPM Maya Kab. Batubara - Agustina Elsera Tarigan; Adelina Sembiring; Lisbet Gurning (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Lower back pain is a common complaint experienced by pregnant women, especially in the second and third trimesters as the gestational age increases. This condition can interfere with daily activities and reduce the quality of life of pregnant women. Pregnancy exercise is one of the non-pharmacological interventions that is believed to help reduce lower back pain. This study aims to analyze the effect of pregnancy exercise on reducing the level of lower back pain in pregnant women in the second and third trimesters. The research method that can be used is a quasi-experimental design with a pre-post test design with one comparison treatment. The research sample was 28 pregnant women in the second and third trimesters who experienced lower back pain and met the inclusion criteria. Measurement of the level of lower back pain will be carried out before and after the intervention period using a valid and reliable pain scale. The data collected will be analyzed using an appropriate statistical test to compare changes in pain levels between before and after the intervention. The results of the study showed that the average lower back pain before the intervention was 3.32 and Std.Deviation 0.772. The average lower back pain after the intervention was 2.25 and Std.Deviation 1.005. Based on the results of bivariate analysis using the Paired-Samples T Test, a significant p value of 0.000 (p <0.05) was obtained, so there is a difference in lower back pain in pregnant women. Thus, it can be said that there is a significant difference in lower back pain before and after pregnancy exercise. It is hoped that the results of this study can provide scientific evidence regarding the effect of pregnancy exercise in reducing lower back pain in pregnant women in the second and third trimesters, so that it can be a recommendation in midwifery care to improve the comfort and quality of life of pregnant women.Keywords: Postpartum exercise, uterine involution, normal delivery